Caffeine affects autonomic control of heart rate and blood pressure recovery after aerobic exercise in young adults: a crossover study - Gonzaga, Luana Almeida (Sci Rep, 2017)
The post-exercise recovery period is associated with changes in autonomic modulation, which can promote an intercurrent-favorable environment. Caffeine has the ability to release catecholamines, but its effects after exercises is little explored. The present study aims to evaluate the acute effects of caffeine on the autonomic control and cardiorespiratory parameters after moderate intensity aerobic exercise. 32 young males (23,59 ± 3,45 years) were submitted to two protocols: Placebo and Caffeine, consisting of 15 minutes of rest, 30 minutes of exercise on a treadmill to 60% on VO2peak, followed by 60 minutes of recovery. Heart rate variability indices and cardiorespiratory parameters were determined at different times during the protocols. The RMSSD and SD1 indices recovered faster in placebo (p < 0.05). The systolic blood pressure differences were found from the 1st to the 5th minute of recovery with the caffeine protocol and from the 1st and 3rd minute with the placebo, whereas, for diastolic blood pressure, significant differences (p < 0.0001) were observed only for the caffeine protocol at the 1st and 3rd minutes of recovery. Caffeine was shown to be capable of delaying parasympathetic recovery but did not influence the behavior of the respiratory rate, oxygen saturation or frequency-domain HRV indices.